The Effect of Perceptual-Motor Exercises on Movement Detection and Motor Coordination among Elderly WomenAim and Background: The purpose of this study was to investigate the effect of perceptual-motor exercises intervention on movement detection and motor - مرتضی طاهری; خدیجه ایران‌دوست; علی همتی عفیف; مینا رضایی (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2018)
Aim and Background: The purpose of this study was to investigate the effect of perceptual-motor exercises intervention on movement detection and motor coordination among aged women. Methods and Materials: In this semi-experimental study, 19 elderly women were randomly assigned into two groups of experimental (n = 10) and control (n = 9). Data were collected using Vienna software. Exercise intervention was perceptual-motor exercises based on Vienna Universal package, including movement detection test and visual pursuit test protocols, which were applied in experimental group 3 sessions a week for 8 weeks. Detection and motor coordination tests were used in pretest and posttest. Analysis of covariance and paired t tests were used to analyze the data. Findings: The mean age of participants was 58.3 ± 4.2 years. Both the movement detection and coordination capabilities were improved in experimental group significantly at posttest (P = 0.001); while no significant change was found in control group. Conclusions: Perceptual-motor exercise can lead to better psychomotor performances such as movement detection and motor coordination.